2008
DOI: 10.1007/s12032-007-9038-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CD23 antigen expression in B-chronic lymphocytic leukaemia and its correlation with clinical parameters

Abstract: B-Chronic lymphocytic leukaemia (B-CLL) is a monoclonal malignancy characterized by an accumulation of terminally differentiated small and anergic B lymphocytes in the blood, bone marrow and other tissues. CD23 antigen, a trans-membrane glycoprotein, promotes the activation and proliferation of normal B lymphocytes and has an important role in the process of malignant transformation in B-CLL. This retrospective cohort study of 77 consecutive newly diagnosed B-CLL patients, 43 males, 34 females, median age of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…However, biologic heterogeneity includes rare CD23 Ϫ cases of CLL, whereas CD23 positivity in MCL is not uncommon. [26][27][37][38] In our test and validation cohorts, 13 of 42 (31%) cases of MCL in leukemic phase were CD23 ϩ , whereas 5 MCL cases in the test cohort had a mini-CLL score of 3. The diagnostic discriminant was useful in such cases with an atypical immunophenotype by combining the information from the CD160FCA on the mini-CLL score and the level of CD23 expression ( Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…However, biologic heterogeneity includes rare CD23 Ϫ cases of CLL, whereas CD23 positivity in MCL is not uncommon. [26][27][37][38] In our test and validation cohorts, 13 of 42 (31%) cases of MCL in leukemic phase were CD23 ϩ , whereas 5 MCL cases in the test cohort had a mini-CLL score of 3. The diagnostic discriminant was useful in such cases with an atypical immunophenotype by combining the information from the CD160FCA on the mini-CLL score and the level of CD23 expression ( Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…Cell staining and FACS analysis of ZAP-70 expression were performed similar to the method described by Crespo et al [16]. Results for CD20, CD23 and FMC7 expression levels were further subgrouped based on the published literature: CD23 was dichotomized to negative/low or high expression subgroups using a cut-off of 50% positive CLL cells [17][18][19]; FMC7 was classified into negative/low or high expression subgroups using a cutoff of 40% positive CLL cells [11]. CD20 and immunoglobulin light chain expression levels were subclasiffied into low, intermediate and high flouresence intensity CLL cells.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Nevertheless, for select antigens significant differences occurred in the percentages of positive neoplastic cells and/or in the antigen density. The most prominent differences were seen in the expression of CD23, CD5 and HLA-DR. [15] reported that the percentage of CD23 positive cells and CD23 antigen expression level is highly variable among CLL/SLL patients. In Juristic's study, the higher percentage of CD23 positive cells was associated with longer survival and lower percentages of CD23 positive cells were seen in the advanced stages of the disease and in patients with high lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%